A Secure Trust based Routing Protocol for Scheme Enhancing Quality of Service in Mobile AdHoc Networks - Sripriya, G.; T. Santha, Dr. (International Journal of Engineering and Technology, 2018)
-Security is an essential requirement for any kind of networking. Security for MANET is more complicated due to its free infrastructure, decentralization and limited resources. So many protocols are designed for the security of MANET. Key management scheme is one of the schemes used in MANET for its high security. In this paper, Threshold based public key management scheme is applied to the On-Demand Vector Routing Protocol for the better performance and high security. Simulation using Network Simulator-2 (NS-2) and under various network conditions shows that threshold based public key management with On-Demand Vector Routing Protocol can greatly improve security and performance in terms of packet delivery ratio, routing overhead and energy consumption.Â